A Fork in the Road? Rethinking Culinary Genius, Power Dynamics, and the Impact of Social Movements on U.S. Food Media and Popular Culture - Julieta Flores Jurado (Norteamérica)
This article aims to enrich our understanding of the political significance of U.S. food media and the evolving dynamics of authority and power within this field. It does so by identifying and describing a sense of fatigue with the paradigm of the genius-chef in U.S. journalism and popular culture, which resonates with wider discussions on sustainability and justice in the restaurant industry. After a brief overview of the conditions that enabled the ascent of chefs to eminence, the article elaborates on how social movements that advocate for systemic analyses of abuse of power (#MeToo and Black Lives Matter) inform the current rejection of the “toxic” chef. Critiques of this figure center on how its cultural appeal has been used to rationalize workplace abuse in the name of culinary perfection. This argument is supported by discussion of a non-fiction book on post-pandemic restaurants, opinion articles, and a television series, The Bear, all published or aired between 2020 and 2023.